Mind, Body, Bubble! Psychological and Biophysical Dimensions of Behavior in Experimental Asset Markets - David Butler; Stephen L. Cheung (Institute of Labor Economics (IZA), 2018)
Asset market bubbles and crashes are a major source of economic instability and inefficiency. Sometimes ascribed to animal spirits or irrational exuberance, their source remains imperfectly understood. Experimental methods can isolate systematic deviations from an asset's fundamental value in a manner not possible on the trading floor. In this chapter, we review evidence from dozens of laboratory experiments that investigate the measurement and manipulation of an array of psychological and biophysical attributes. Measures of emotion self-regulation and interoceptive ability are informative, as is cognitive ability and the level and fluctuation of hormones. Rules that promote deliberative decision making can improve market efficiency, while incidental emotions can impair it. Signals in specific brain areas can be a trigger precipitating a bubble's collapse. We conclude that trading decisions are profoundly biophysical in a manner not captured by efficient markets models, and close with speculations on implications for algorithmic trading.
Keywords: C92; D91; G12; G41; 330; efficient markets hypothesis; emotions; experimental asset markets; price bubbles and crashes; somatic marker hypothesis